เปิดประเด็น: นวัตกรรมการจัดการเรียนรู้เชิงบูรณาการนอกห้องเรียน: เปิดห้องเรียนสู่แหล่งเรียนรู้ - ใจรักษ์ศักดิ์, พรรณงาม (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract Within the context of the country and the world constantly changing to prepare people to face a variety of sittuations educational management must be developed and create flexible learning styles and be adaptable to suit well all such changes at any time. Innovative integrated learning outside the classroom by opening the classroom to access new resources or new knowledge is another way to help students learn from a vast variety of sources. Most learning resources have important information or content with various media that are relevent to the context of the student’s topic of study or any given projects. Connecting classroom lessons to learning resources outside the classroom will open the world of endless learning for students to learn something about reality and different kinds of content. Technology advances help connect the classroom to the outside world more conviniently. Collecting a variety of learning resources, developing and creating resources within school gain more understanding and ability to design and planning the learning resources for responding to the needs of students, all of these will be provided and prepare student to find their potential and success with their study’s goal and have the ability to face the real world outside school.